-
Notifications
You must be signed in to change notification settings - Fork 0
/
Copy pathLemma2-4-Bij-A.agda
324 lines (276 loc) · 15.5 KB
/
Lemma2-4-Bij-A.agda
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
74
75
76
77
78
79
80
81
82
83
84
85
86
87
88
89
90
91
92
93
94
95
96
97
98
99
100
101
102
103
104
105
106
107
108
109
110
111
112
113
114
115
116
117
118
119
120
121
122
123
124
125
126
127
128
129
130
131
132
133
134
135
136
137
138
139
140
141
142
143
144
145
146
147
148
149
150
151
152
153
154
155
156
157
158
159
160
161
162
163
164
165
166
167
168
169
170
171
172
173
174
175
176
177
178
179
180
181
182
183
184
185
186
187
188
189
190
191
192
193
194
195
196
197
198
199
200
201
202
203
204
205
206
207
208
209
210
211
212
213
214
215
216
217
218
219
220
221
222
223
224
225
226
227
228
229
230
231
232
233
234
235
236
237
238
239
240
241
242
243
244
245
246
247
248
249
250
251
252
253
254
255
256
257
258
259
260
261
262
263
264
265
266
267
268
269
270
271
272
273
274
275
276
277
278
279
280
281
282
283
284
285
286
287
288
289
290
291
292
293
294
295
296
297
298
299
300
301
302
303
304
305
306
307
308
309
310
311
312
313
314
315
316
317
318
319
320
321
322
323
324
open import Relation.Nullary.Core
open import Relation.Nullary.Decidable
open import Relation.Binary.Core
open import Relation.Binary.PropositionalEquality as PropEq hiding (proof-irrelevance)
open import Data.Empty
open import Data.Unit hiding (_≤?_; _≤_; _≟_)
open import Data.Product
open import Data.Bool hiding (_≟_)
open import Data.Nat hiding (compare) renaming (_≟_ to _ℕ≟_)
--open Data.Nat.≤-Reasoning
--open import Function.Inverse
open import Data.Sum
open import Data.Nat.Properties
open SemiringSolver
open import Function hiding (_∘_)
open import Function.Equality hiding (_∘_) renaming (cong to Icong)
open import Function.Inverse renaming (sym to Isym; zip to Izip; id to Iid)
open import Function.LeftInverse hiding (_∘_)
open import Function.Bijection hiding (_∘_)
import Data.Fin as F
import Data.Fin.Props as F
open import Function.Related.TypeIsomorphisms
import Relation.Binary.Sigma.Pointwise as SP
open import Function.Equivalence hiding (sym)
open import FinBijections
open import Data.Vec hiding ([_])
open import Misc
open import Lemma2-4-Inv
module Lemma2-4-Bij-A where
ρ-fin : (e f : P) → F.Fin ⌈ suc n /2⌉
ρ-fin e f = F.fromℕ≤ {ρ e f} (s≤s A₁'-ρ)
where open Data.Nat.≤-Reasoning
lem-ρ-fin : ∀ {e f} → F.toℕ (ρ-fin e f) ≡ ρ e f
lem-ρ-fin {e} {f} = F.toℕ-fromℕ≤ (s≤s A₁'-ρ)
ρ≥1 : ∀ {e f r} → (ρ≡r : ρ e f ≡ r) →
{≥1 : True (1 ≤? r)} → True (1 ≤? ρ e f)
ρ≥1 refl {x} = x
bij₁ : ∀ {e f r} → (ρ≡r : ρ e f ≡ r) → {≥1 : True (1 ≤? r)}
{<n : True (suc r ≤? ⌈ n /2⌉)} →
K e f (pred r) ↔ Σ (Neck e) (λ nck → nck ≡ neck⋆ e f {ρ≥1 ρ≡r})
bij₁ {e} {f} {._} refl {≥1} {<n} = Σ↔ Iid (λ {x} →
record { to = record
{ _⟨$⟩_ = to ; cong = cong (to {x}) };
from = record
{ _⟨$⟩_ = from ; cong = cong from } })
where
postulate Σ↔ : predicate-irrelevant-Σ↔
to : {nck : Neck e} →
(neck-e₂ nck ≢ e × ρ (neck-e₂ nck) f ≡ pred (ρ e f))
→ nck ≡ neck⋆ e f
to {nck} ( ≢e , ρ≡) = neck! (≢sym ≢e)
(0<ρ<n/2⁻¹.class-A nck
ρ≡ (≢sym ≢e))
from : {nck : Neck e} → nck ≡ neck⋆ e f →
neck-e₂ nck ≢ e × ρ (neck-e₂ nck) f ≡ pred (ρ e f)
from {nck} ≡⋆ = ((λ eq → lem-neck⋆ (sym $ subst (λ z → e ≡ neck-e₂ z) ≡⋆
(sym eq))) , 0<ρ<n/2.class-A-ρ
{≥1 = ≥1}
{<n = <n}
nck (cong neck-e₂ ≡⋆))
bij₂ : ∀ {e f r} → (ρ≡r : ρ e f ≡ r) → {≥1 : True (1 ≤? r)}
{<predn : True (suc r ≤? ⌈ (pred n) /2⌉)} →
K e f r ↔ Σ (Neck e)
(λ nck →
((neck-e₁ nck) ≡ (neck-e₁ (neck⋆ e f {ρ≥1 ρ≡r})) ×
(neck-e₂ nck) ≢ (neck-e₂ (neck⋆ e f {ρ≥1 ρ≡r}))) ×
e ≢ (neck-e₂ nck))
bij₂ {e} {f} {._} refl {≥1} {<predn} =
Σ↔ Iid
(λ {x} →
record
{ to = record {
_⟨$⟩_ = to {x} ; cong = cong (to {x}) };
from = record {
_⟨$⟩_ = from {x} ; cong = cong (from {x})}})
where open Data.Nat.≤-Reasoning
postulate Σ↔ : predicate-irrelevant-Σ↔
<n : True (suc (ρ e f) ≤? ⌈ n /2⌉)
<n = fromWitness (begin
suc (ρ e f)
≤⟨ toWitness <predn ⟩
⌈ pred n /2⌉
≤⟨ ⌈n/2⌉-mono (≤⇒pred≤ n n m≤m) ⟩
(⌈ n /2⌉ ∎))
to : {nck : Neck e} → (neck-e₂ nck ≢ e ×
ρ (neck-e₂ nck) f ≡ (ρ e f)) →
((neck-e₁ nck) ≡ (neck-e₁ (neck⋆ e f)) ×
(neck-e₂ nck) ≢ (neck-e₂ (neck⋆ e f))) × e ≢ (neck-e₂ nck)
to {nck} (≢e , ρ≡) = (0<ρ<predn/2⁻¹.class-B
nck ρ≡ (≢sym ≢e) , (≢sym ≢e))
from : {nck : Neck e} → ((neck-e₁ nck) ≡ (neck-e₁ (neck⋆ e f)) ×
(neck-e₂ nck) ≢ (neck-e₂ (neck⋆ e f))) ×
e ≢ (neck-e₂ nck) → (neck-e₂ nck ≢ e ×
ρ (neck-e₂ nck) f ≡ (ρ e f))
from {nck} ((≡e₁⋆ , ≢e₂⋆) , ≢e) = ((≢sym ≢e) ,
(0<ρ<n/2.class-B-ρ nck
≡e₁⋆ ≢e₂⋆
(≢sym ≢e)))
bij₃ : ∀ {e f r} → (ρ≡r : ρ e f ≡ r) → {≥1 : True (1 ≤? r)}
{<predn : True (suc r ≤? ⌈ (pred n) /2⌉)} →
K e f (suc r) ↔ Σ (Neck e)
(λ nck →
(proj₁ nck) ≢ (proj₁ (neck⋆ e f {ρ≥1 ρ≡r})) ×
e ≢ (neck-e₂ nck))
bij₃ {e} {f} {._} refl {≥1} {<predn} = Σ↔ Iid
(λ {x} →
record
{ to = record {
_⟨$⟩_ = to {x} ; cong = cong (to {x})}
; from = record {
_⟨$⟩_ = from {x} ; cong = cong (from {x})}
})
where open Data.Nat.≤-Reasoning
postulate Σ↔ : predicate-irrelevant-Σ↔
<n : True (suc (ρ e f) ≤? ⌈ n /2⌉)
<n = fromWitness (begin
suc (ρ e f)
≤⟨ toWitness <predn ⟩
⌈ pred n /2⌉
≤⟨ ⌈n/2⌉-mono (≤⇒pred≤ n n m≤m) ⟩
(⌈ n /2⌉ ∎))
to : {nck : Neck e} → (neck-e₂ nck ≢ e ×
ρ (neck-e₂ nck) f ≡ suc (ρ e f)) →
(proj₁ nck) ≢ (proj₁ (neck⋆ e f)) ×
e ≢ (neck-e₂ nck)
to {nck} (≢e , ρ≡) = ((λ eq →
0<ρ<predn/2⁻¹.class-C
nck ≢e ρ≡ (cong el eq)) , ≢sym ≢e)
from : {nck : Neck e} → (proj₁ nck) ≢ (proj₁ (neck⋆ e f)) ×
e ≢ (neck-e₂ nck) → (neck-e₂ nck ≢ e ×
ρ (neck-e₂ nck) f ≡ suc (ρ e f))
from {nck} (≢e₁⋆ , ≢e) = (≢sym ≢e ,
(0<ρ<n/2.class-C₀-ρ nck
(λ eq → ≢e₁⋆ (Σ'≡ eq))
(≢sym ≢e)
(toWitness <predn)))
predn-≥1 : ∀ {e f} → ρ e f ≡ ⌈ (pred (n)) /2⌉ → ρ e f ≥ 1
predn-≥1 {e} {f} ≡predn = (begin 1 ≤⟨ s≤s z≤n ⟩ ⌈ pred n /2⌉
≡⟨ sym ≡predn ⟩ (ρ e f ∎))
where open Data.Nat.≤-Reasoning
bij₄ : ∀ {e f r} → (ρ≡r : ρ e f ≡ r)
{≡predn/2 : True (r ℕ≟ ⌈ (pred (n)) /2⌉)} {oddn : Odd n} →
K e f r ↔ Σ (Neck e)
(λ nck →
nck ≢ (neck⋆ e f
{fromWitness (predn-≥1
(trans ρ≡r (toWitness ≡predn/2)))}) ×
(neck-e₂ nck) ≢ e)
bij₄ {e} {f} {._} refl {≡predn} {oddn} =
Σ↔ Iid (λ {x} →
record
{ to = record { _⟨$⟩_ = to {x} ; cong = cong (to {x}) }
; from = record { _⟨$⟩_ = from {x} ; cong = cong (from {x}) }})
where open Data.Nat.≤-Reasoning
postulate Σ↔ : predicate-irrelevant-Σ↔
≥1 : True (1 ≤? ρ e f )
≥1 = fromWitness (begin 1 ≤⟨ s≤s z≤n ⟩ ⌈ pred n /2⌉
≡⟨ sym (toWitness ≡predn) ⟩ (ρ e f ∎))
<n : True (suc (ρ e f) ≤? ⌈ n /2⌉)
<n = fromWitness
(begin suc (ρ e f)
≡⟨ cong suc (toWitness ≡predn) ⟩
suc ⌈ pred n /2⌉
≡⟨ cong suc (helper oddn) ⟩
suc (pred ⌈ n /2⌉) ≡⟨ refl ⟩ (⌈ n /2⌉ ∎))
where helper : ∀ {x} → Odd x → ⌈ pred x /2⌉ ≡ pred ⌈ x /2⌉
helper {zero} ox = refl
helper {suc zero} ox = refl
helper {suc (suc m)} (oddSuc ox) = sym (lem-even⇒⌊≡⌋
(oddEven ox))
to : {x : Neck e} → (neck-e₂ x ≢ e × ρ (neck-e₂ x) f ≡ ρ e f) →
(x ≢ neck⋆ e f {≥1} × neck-e₂ x ≢ e)
to {nck} proof = (λ eq → ρ≡1/2-predn⁻¹.class-B
{ρ≡ = ≡predn} nck (proj₂ proof)
(≢sym (proj₁ proof)) (cong neck-e₂ eq)) ,
(proj₁ proof)
from : {x : Neck e} → (x ≢ neck⋆ e f {≥1} × neck-e₂ x ≢ e) →
(neck-e₂ x ≢ e × ρ (neck-e₂ x) f ≡ ρ e f)
from {nck} proof with pt (neck-e₂ nck) ≟ pt (neck-e₂ (neck⋆ e f ))
...| yes p =
⊥-elim (proj₁ proof (neck! {nck = nck}
{nck' = neck⋆ e f }
(≢sym $ proj₂ proof) (pt-inj p)))
... | no ¬p with ln (neck-e₁ nck) ≟ ln (neck-e₁ (neck⋆ e f))
... | yes p =
(proj₂ proof) , (0<ρ<n/2.class-B-ρ
nck (ln-inj p)
(λ eq → ¬p (cong pt eq))
((proj₂ proof)))
... | no ¬p₁ = (proj₂ proof) ,
(0<ρ<n/2.class-C₁-ρ nck
(λ eq → ¬p₁ (cong ln eq))
(λ eq → ¬p (cong pt eq))
((proj₂ proof)) (toWitness ≡predn))
bij₅ : ∀ {e f r} → (ρ≡r : ρ e f ≡ r) {≡predn/2 : True (r ℕ≟ ⌈ n /2⌉)}
{evenn : Even n} → K e f (pred r) ↔
(Σ (Neck e) (λ nck →
(neck-e₂ nck) ≡ ρ≡n/2.e₂⋆
{n-even = evenn }
{≡n/2 = fromWitness
(trans ρ≡r (toWitness ≡predn/2))}
(proj₁ nck)))
bij₅ {e} {f} {._} refl {≡predn} {n-even} =
Σ↔ Iid (λ {x} → record
{ to = record { _⟨$⟩_ = to {x} ; cong = cong (to {x}) }
; from = record { _⟨$⟩_ = from {x} ; cong = cong (from {x}) } })
where
postulate Σ↔ : predicate-irrelevant-Σ↔
to : {x : Neck e} → (neck-e₂ x ≢ e ×
ρ (neck-e₂ x) f ≡ pred (ρ e f)) →
neck-e₂ x ≡
ρ≡n/2.e₂⋆ {n-even = n-even} (proj₁ x)
to {x} proof = ρ≡n/2⁻¹.class-A₀ {n-even = n-even}
x (trans (proj₂ proof)
(cong pred (toWitness ≡predn)))
from : {x : Neck e} → neck-e₂ x ≡ ρ≡n/2.e₂⋆ {n-even = n-even} (proj₁ x) →
(neck-e₂ x ≢ e × ρ (neck-e₂ x) f ≡ pred (ρ e f))
from {x} proof =
(λ eq → ρ≡n/2.lem-e₂⋆ {n-even = n-even}
{≡n/2 = ≡predn}
{l#e = proj₁ x}
(trans (sym proof) eq)) ,
(trans (ρ≡n/2.class-A₀-ρ
{n-even = n-even}
{≡n/2 = ≡predn} x proof)
(sym $ cong pred (toWitness ≡predn)))
bij₆ : ∀ {e f r} → (ρ≡r : ρ e f ≡ r) {≡predn/2 : True (r ℕ≟ ⌈ n /2⌉)}
{evenn : Even n} →
K e f r ↔ (Σ (Neck e)
(λ nck → (neck-e₂ nck) ≢ ρ≡n/2.e₂⋆
{n-even = evenn }
{≡n/2 = fromWitness (trans ρ≡r (toWitness ≡predn/2))}
(proj₁ nck) × (neck-e₂ nck) ≢ e))
bij₆ {e} {f} {._} refl {≡predn} {n-even} =
Σ↔ Iid (λ {x} → record
{ to = record { _⟨$⟩_ = to {x} ; cong = cong (to {x}) }
; from = record { _⟨$⟩_ = from {x} ; cong = cong (from {x}) } })
where postulate Σ↔ : predicate-irrelevant-Σ↔
to : {x : Neck e} → (neck-e₂ x ≢ e × ρ (neck-e₂ x) f ≡ ρ e f) →
(neck-e₂ x) ≢ ρ≡n/2.e₂⋆
{n-even = n-even} (proj₁ x) × neck-e₂ x ≢ e
to {x} proof = (ρ≡n/2⁻¹.class-A₁ {n-even = n-even} x
(trans (proj₂ proof) (toWitness ≡predn))) , (proj₁ proof)
from : {x : Neck e} → (neck-e₂ x) ≢ ρ≡n/2.e₂⋆
{n-even = n-even} (proj₁ x) × neck-e₂ x ≢ e →
(neck-e₂ x ≢ e × ρ (neck-e₂ x) f ≡ ρ e f)
from {x} proof = (proj₂ proof) ,
(trans (ρ≡n/2.class-A₁-ρ {n-even = n-even} x
(proj₁ proof)) (sym (toWitness ≡predn)))
bij₀ : ∀ {e f} → ρ e f ≡ 0 →
K e f 1 ↔ (Σ (Neck e) (λ nck → (neck-e₂ nck) ≢ e))
bij₀ {e} ρ≡0 rewrite (sym $ ρ≡0⇒e≡f ρ≡0) =
Σ↔ Iid (λ {x} → record
{ to = record { _⟨$⟩_ = to {x} ; cong = cong (to {x}) }
; from = record { _⟨$⟩_ = from {x} ; cong = cong (from {x}) }})
where
postulate Σ↔ : predicate-irrelevant-Σ↔
to : {x : Neck e} → (neck-e₂ x ≢ e ×
ρ (neck-e₂ x) e ≡ 1) → neck-e₂ x ≢ e
to {x} proof = proj₁ proof
from : {x : Neck e} → neck-e₂ x ≢ e →
(neck-e₂ x ≢ e × ρ (neck-e₂ x) e ≡ 1)
from {x} proof = proof , ρe₂e≡1
where e₂ = proj₂ x
e₁ = proj₁ x
x≤1⇒x≡0or1 : ∀ {x} → x ≤ 1 → (x ≡ 0) ⊎ (x ≡ 1)
x≤1⇒x≡0or1 z≤n = inj₁ refl
x≤1⇒x≡0or1 (s≤s z≤n) = inj₂ refl
ρe₂e≤1 : ρ (el e₂) e ≤ 1
ρe₂e≤1 = sppc-ρ-shorter-than
((((el e₁) ∶ (#sym (pf e₂))) ,
(e ∶ (#sym (pf e₁)))) ∷ [ e ])
ρe₂e≡1 : ρ (el e₂) e ≡ 1
ρe₂e≡1 with x≤1⇒x≡0or1 (ρe₂e≤1)
ρe₂e≡1 | inj₁ x≡0 = ⊥-elim (proof (ρ≡0⇒e≡f x≡0))
ρe₂e≡1 | inj₂ x≡1 = x≡1